The Use of Fluorine to Protect β-Solidifying γ-TiAl-Based Alloys against High-Temperature Oxidation. (13th February 2017) - Donchev, Alexander; Galetz, Mathias; Mayer, Svea; Clemens, Helmut; Schütze, Michael
ABSTRACT: Light-weight alloys based on intermetallic titanium aluminides (TiAl) are structural materials considered for high-temperature applications, e.g. in aero engines or automotive engines. TiAl alloys of engineering interest consist of two phases, the γ-TiAl and the α2 -Ti3 Al-phase. Recent developments have led to the so-called TNM alloys (T = TiAl; N = Nb; M = Mo) with an Al-content of 43.5 at.%. These alloys also possess the disordered body centered cubic β-Ti(Al)-phase at elevated temperatures, which ensures a better hot-workability compared to conventional two-phase alloys. However, the relatively low Al content (< 45 at.%) limits the high-temperature capability due to reduced oxidation resistance. This impedes their application in a temperature range above 800°C. The present work shows how the fluorine effect counteracts this disadvantage due to the formation of a protective alumina layer. The performance of the TNM alloy with the nominal composition of Ti-43.5Al-4Nb-1Mo-0.1B (at.%) is compared with another TNM alloy variant containing additional elements, such as Si and C, and the so-called GE alloy (Ti-48Al-2Cr-2Nb; at.%), which is already in use for turbine blades. The results of isothermal and thermocyclic high-temperature exposure tests of untreated and fluorine treated specimens will be compared. The effect of composition and microstructure of the alloys on the oxidation behavior with and without fluorine treatment are discussed.